The mediating effect of perceiving close relatives as obese on obesity and weight control behavior score among adults: An exploratory cross-sectional study in Chongqing, China - Wu, Tingting; Liu, Weiwei; Chen, Yifan; Guo, Tian; Sun, Rong (Frontiers in Public Health, 2022)
Obesity is one of the most blatantly visible-yet most neglected public health problems facing the world faces. Individuals’ self-perception of their overweight is essential to initiate weight control. This is the first exploratory study in Chongqing to assess the mediating effect of perceived obesity in close relatives on obesity and weight control behavior among adults. A cross-sectional study, including 3,7492 participants was conducted in a health care center of a hospital in Chongqing, China. Kruskal-Wallis test analyses, logistic regression, and Sobel-Goodman mediation tests were employed. Only 1.76% of participants (660) were detected as obese by a doctor and only 2.13% of participants (798) thought their close relatives were obese. Nearly 1/3 of the participants consumed more than twice the amount of the recommended daily intake of meat. More than 85% of participants lacked exercise. Obesity was positively associated with obesity perception in close relatives (OR = 19.556, P < 0.001). The association between the respondent’s obesity status and weight control behavior scores was statistically significantly changed (β = 0.594, P < 0.001). Individuals perceiving relatives as obese were more like to engage in weight control behavior (β = 0.678, P = 0.001). The obesity perception in close relatives played a partial mediating effect in the association of obesity and weight control behavior (ab=0.141, SE=0.03, 95%CI= 0.086,0.198). Obese individuals are more likely to engage in weight control behavior, and the effect of individuals' obesity status on weight control behavior scores is partially mediated by the obesity perception in close relatives among the participants. Findings suggest that personal obesity status perception of close relatives might provide new weight management ideas for the health care centers.